Gambaran Pengetahun Personal Hygien Pada Anak Sekolah Dasar - Nitsae, Veronika; Sanan, Yane Cristiana Ua; Rohi, Elfrida Dana Frederita Riwoe (Jurnal Borneo Cendekia, 2025)
Health problems among elementary school-aged children remain common due to their vulnerability to various diseases. Poor hygiene practices, such as improper tooth brushing, hand washing without soap, consuming unhealthy foods, and neglecting personal hygiene, are significant risk factors for infectious diseases. Knowledge plays a vital role in influencing personal hygiene practices. This study aims to assess schoolchildren's knowledge of personal hygiene. The research design used was descriptive, aiming to determine the level of knowledge about personal hygiene among elementary school children at Sadi Catholic Elementary School in 2024. The population included 79 students from grades 4, 5, and 6, selected through a total sampling method. The instrument was a questionnaire with 37 questions. Results indicated that the knowledge level of elementary school children about personal hygiene at Sadi Catholic Elementary School was categorized as good (38%), sufficient (51%), and poor (11%). Based on these findings, it can be concluded that most elementary school children had sufficient knowledge about personal hygiene.